1991
DOI: 10.1080/02652039109373953
|View full text |Cite
|
Sign up to set email alerts
|

Production of mycotoxins by selectedFusarium graminearumandF. crookwellenseisolates

Abstract: Corn cultures (five isolates each of Fusarium graminearum Group 1 from wheat crowns, Group 2 from scabby wheat grains and from ear rot of corn and five isolates of F. crookwellense) were screened for their ability to produce deoxynivalenol (DON), nivalenol (NIV), fusarenon-x (FUS-X) and zearalenone (ZEA). Nine of the ten F. graminearum isolates from wheat produced DON (5-165 micrograms g-1) but none produced either NIV or FUS-X. Conversely, 3/5 and 2/5 of the F. graminearum isolates from corn produced NIV (5-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…According to their trichothecene production, some Fusarium species, such as F graminearum, have been divided into two chemotypes: (i) the nivalenol chemotype, which includes isolates producing nivalenol and fusarenone X, and (ii) the deoxynivalenol chemotype, which includes isolates producing deoxynivalenol and acetyldeoxynivalenol (26,53). Similar observations have been made for F. culmorum strains (28, 39).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…According to their trichothecene production, some Fusarium species, such as F graminearum, have been divided into two chemotypes: (i) the nivalenol chemotype, which includes isolates producing nivalenol and fusarenone X, and (ii) the deoxynivalenol chemotype, which includes isolates producing deoxynivalenol and acetyldeoxynivalenol (26,53). Similar observations have been made for F. culmorum strains (28, 39).…”
supporting
confidence: 58%
“…In addition, it has been demonstrated that, within the same species and in the same culture conditions, toxin production by Fusarium strain may vary sharply; some strains produce large amounts of trichothecenes, whereas others produce small or undetectable amounts of trichothecenes (3,5,19,28,30,35,36,39,53,57). Until now, no method except in vitro culture has been available to distinguish high-producing from low-producing Fusarium strains.…”
mentioning
confidence: 99%
“…It is reported that both DON and NIV have been found in wheat and barley (Ichinoe et al 1983;Yoshizawa et al 1979;Sydenham et al 1991) and co-contaminated the same maize (Okoye 1993), leading to research of the risk Concentration-dependent effects of NIV on LPS-induced NO production by RAW264 cells in the presence of DON RAW264 cells were stimulated with NIV (0-3,000 nmol/l) in the presence of LPS (100 ng/ml) and DON (600 nmol/l) for 24 h. The culture supernatants were analyzed for NO levels. Values are the means ± SEM from four independent experiments.…”
Section: Discussionmentioning
confidence: 96%
“…These chemotypes appear to differ in geographic distribution. The NIV chemotype has been reported in several countries of Africa, Asia, and Europe (10,14,22,35,37), but it has not been reported in North America (1,27). Since the NIV chemotype is of great concern in the countries where it has appeared, an efficient system for differentiating DON and NIV chemotypes is desired.…”
mentioning
confidence: 99%